Bimbingan Teknis Pengawasan Koperasi Se-Kabupaten Bengkayang Tahun 2019: Manajemen Pengawasan Koperasi - Sabinus Beni; Blasius Manggu (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2019)
The implementation of the Technical Guidance for Supervision of Cooperative Supervision of Bengkayang Regency is carried out by the Department of Cooperatives, Small and Medium Enterprises, Labor, and Transmigration of Bengkayang Regency in responding to the conditions of 189 Cooperatives in Bengkayang Regency with 125 Active Cooperatives and only 24 Cooperatives that have conducted Annual Member Meetings. The purpose of this activity is to provide technical guidance to 30 cooperative supervisors to be able to maximize the oversight function so that 125 cooperatives actively carry out the Annual Member Meeting. The method of implementing the activity begins with the presentation of material and questions and answers. In general, participants understood about cooperative supervision management material and committed to implementing it, especially by encouraging each cooperative's management and employees to hold annual Member Meetings regularly.